The Challenges of Educational Philosophies in the Cultural Space of Latvia - Jurs, Pavels; Klasone, Inta (European Scientific Journal, ESJ, 2017)
The authors of the publication have updated the importance of the philosophy of education in the cultural space of Latvia. This study has gained significance within the context of personal development and teacher professionalism. However, existing tendencies and regulatory frameworks must be taken into account. In the context of educational theory a topical issue is: How to implement the teaching purposefully according with the external and internal factors and the influence of individual’s psychological processes and at the same time maintaining the continuity and succession and providing support for the harmonious and comprehensive development of personality? The author’s propose that by implementing a regulatory framework and the analysis of theoretical literature, to evaluate and update, the importance of teacher’s professional dispositions their educational philosophy, and being mindful of the personality formation will lend to a balanced educational process. The 21st century is characterized by dynamism and rapid change, which consists of both benefits and challenges, e.g. increasing international competition, migration and multiculturalism, technological progress etc. That is reinforced by the transformation of sociocultural, humanitarian crisis and the revision of fundamental cultural values (Alijevs, 2005. Thus teacher`s and student`s interaction gains importance and being aware of that through recognizing the social and environmental challenges and the features of personal development, diverse educational process, different types of support is provided to students and their competitiveness and competences are promoted.